The effect of Using Innovative Tool for Learning reverse forehand and backhand in Badminton for female students - Maki, Ali; Mahdi, Mustafa (Journal of Physical Education, 2018)
The effect of Using Innovative Tool for Learning reverse forehand and backhand in Badminton for female studentsThe importance of research lies in the design of an innovative too, preparing a number of exercises using this tool and studying its effect on the learning of forehand and backhand skills in badminton. The problem of this research is that the beginners have some learning difficulties on the basic badminton skills by sticking with traditional learning using a partner or the wall for executing the exercise without using modern devices. The research aimed at designing innovative tool and using it for teaching some basic skills for female badminton students. The researcher used the experimental method and the sample of the research was on a group of female students in the first stage, which included 32 students from two classes chosen randomly. The exercises were applied by the researcher using the designed devices on the second group to determine the level of improvement that occurs for the students in the performance of the studied skills. Based on the results obtained by the researcher, the most important conclusions are the innovative tools used in this study were suitable for the level of students and their abilities and also suitable for the improvement in learning the forehand and backhand badminton skills. Finally the researcher recommended teaching the learning how the tool works to develop the accuracy and performance of beginners.